Therapeutic Effects of Transplanted Exosomes Containing miR-29b to a Rat Model of Alzheimer’s Disease - Jahangard, Yavar; Monfared, Hamideh; Moradi, Arman; Zare, Meysam; Mirnajafi-Zadeh, Javad; Mowla, Seyed Javad (Frontiers in Neuroscience, 2020)
Alzheimer's disease (AD) is a complex neurodegenerative disorder with no definite treatment. The expression of miR-29 family is significantly reduced in AD, suggesting a part for the family members in pathogenesis of the disease. The recent emergence of microRNA (miRNA)-based therapeutic approaches is emphasized on the efficiency of miRNA transfer to target cells. The endogenously-made secretory vesicles could provide a biological vehicle for drug delivery. Characteristics such as small sizes, the ability to cross the blood-brain barrier, the specificity in binding to the right target cells, and most importantly the capacity to be engineered as drug carriers have made exosomes desirable vehicles to deliver genetic materials to the central nervous system. Here, we transfected rat bone marrow stem cells (r-BMSC) and HEK-293T cells with recombinant expression vectors, carrying either mir-29a or mir-29b precursor sequences. A significant overexpression of miR-29 and down-regulation of their targets genes: BACE1 and BIM were confirmed in the transfected cells. Then, we confirmed the packaging of miR-29 in exosomes secreted from the transfected cells. Finally, we investigated a possible therapeutic effect of the engineered exosomes to reduce the pathological effects of Aβ in a rat model of AD. Aβ-treated model rats showed some deficits in spatial learning and memory. However, in animals injected with miR-29-containing exosomes at CA1, the aforementioned impairments were prevented. In conclusion, our findings provide a new approach for the packaging of miR-29 in exosomes and that the engineered exosomes might have a therapeutic potential in AD.